Comparison of the quality of jelly from ripe and unripe kamias (Averrhoa bilimbi) applied with agar and gelatin. - Baldo, Micaella Patricia Darang
The utilization of agar and gelatin as gelling agents for the production of unripe and ripe kamias jellies was investigated in terms of physicochemical, texture, and sensorial attributes. The physicochemical analyses performed include total soluble solids (TSS), pH, and % titratable acidity (TA) as oxalic acid. There were significant (P=0.00) interactions between degree of ripeness and gelling agents affecting the TSS (at 22-25 °Bx), pH (at6 3.25), and TA (at 0.47%) of the kamias jelly. Unripe gelatin-treated kamias jelly had a mean TSS of 31.6 °Bx, pH of 3.28, and TA of 0.48%. Ripe gelatin-treated kamias jelly had a mean TSS of 30.7 °Bx, pH of 3.31, and TA of 0.46%. In relation to the texture profile, the hardness, only unripe and ripe agar-treated kamias jellies exhibited a non-significant difference from the commercial jellies. With regards to the % deformation at hardess, unripe agar-treated jelly and both unripe and ripe gelatin-treated kamias jellies showed non-significant difference from the commercial jelly. Sensory evaluation tests demonstrated that unripe gelatin-treated jellies had more perceptible sweetness and firmness than the agar-treated jellies. For the ripe kamias jellies, gelatin-treated jellies showed mor perceptible sweetness and kamias flavor than the agar-treated jellies. A significant difference was observed on the preference between the unripe and ripe agar-treated jellies using Mann-Whitney Test at 95% confidence level, with the unripe kamias jellies being more preferred. The consumer acceptability of this jelly was found to be 'like moderately' which was similar to the acceptability of the unripe gelatin-treated kamias jelly.